Comparative Analysis of Circular Economy Pilot Projects in the Danube Region - Medved, Tilen; Kutnjak, Ana; Urh, Benjamin (45th International Conference on Organizational Science Development: Organization and the Longevity Society, Conference Proceedings, 2026)
Circular economy pilot projects are an important tool for sustainable transitions, but their diversity makes it difficult to compare and transfer results. This paper presents a comparative analysis of eight circular economy pilot projects in the Danube region, covering the textile, packaging, smart city, e-waste, and food and agriculture sectors. In all cases, a uniform documentation and modeling framework was used, which included common templates, multi-perspective modeling, and a centralized repository. Based on a comparative analysis, we conclude that, despite their different contexts, the pilots share similar goals and challenges, such as ensuring a stable supply of secondary materials, high initial costs, regulatory requirements, and limited market acceptance. Key success factors include partner networks, return systems, and local support. The paper shows that standardized documentation enables the identification of recurring patterns of challenges and success factors across sectors, thereby supporting comparability, knowledge transfer, and evidence-based decision-making in the circular economy.